SYSTEM ANALYSIS IN LANGUAGE TEAHING AND LEARNING IN TECHNICAL UNIVERSITY - Tatiana V. Sidorenko; Vladimir Z. Yampolsky (Открытое образование (Москва), 2016)
The article reviews the current situation and trends in the development of the language education in Russian technical universities, as well as the challenges towards its improvement. There set forth the goals and objectives of the foreign-language training system development, whereof the interdisciplinarity, modularity, networking and linguistic authenticity are of prime importance. Terms and conditions of the system performance effectiveness are specified and the concept of its generation is evaluated. As a result of the system research a model of the language education organization and management in a technical university is suggested.